Development of hand tractor-mounted seed drill for rice-based cropping systems in the Philippines - Bautista, Elmer G.; Gagelonia, Eden C.; Abon, John E.; Corales, Aurora M.; Bueno, Crisanta S.; Banayo, Niño P.M.C.; Lugto, Roman V.; Suralta, Roel R.; Kato, Yoichiro (Informa UK Limited, 2019)
Dry direct-seeded rice is widely practiced in drought-prone environments in tropical Asia where mechanized options for crop establishment are in great demand. The objective of this study is to identify the suitable design of a hand tractor-mounted multigrain seed drill under biophysical conditions in the Philippines. The prototype was newly designed and tested under field conditions in three provinces in 2015 and 2016. The results suggested that the prototype with tined furrow openers and an inclined circular seed plate in the hopper for seed metering driven by the ground wheel through the combination of chain and sprocket produced rice grain yield similar to the crop established from broadcasting. Field experiments also confirmed that the seed drill has a capacity of over 2 ha day−1 for rice and over 3 ha day−1 for mung bean, and thus, the prototype appears promising for rainfed lowlands in the Philippines.